What is the minimum value for g(x) = x^2 – 10x + 16?

would it be 2?

Answers

Answer 1
Answer: vertex aka mn or max value when you have
f(x)=ax^2+bx+c
vertex=-b/2a

a=1
b=-10
-b/2a
-(-10)/2(1)=10/2 =5

min value is 5
sub 5 for x
5^2-10*5+16
25-50+16
-9
min point is (5,-9)

Related Questions

Danae is choosing between two jobs. One job pays an annual bonus of $1,500 plus $120 per day worked. The second job pays a annual bonus of $2,500 plus $100 per day worked.120d + 1,500=100d+ 2,500 d=100 How much will Danae have earned on day 100 at either job? A: 12,000 B:12,500 C:13,500 D:14,500
What is the general form of the equation of the line shown?
QUESTION 23 Determine if the given solution is correct. If it is not, find the solution. Is -5 the solution to x+6=5-4? no; x=7 yes no; x=3 no; x=15
Solve the equation s + 2.8 = 6.59
how do you explain the midpoint of cd is e (-1,0). one endpoint is c(5,2). what are the coordinates of the other endpoint?

Jayden’s new puppy weighed 11 and one fourth pounds at 4 weeks old. At four weeks, the puppy weighed three fifths times as much as at 16 weeks. Which equation can be used to find how much Jayden’s puppy weighs at 16 weeks old

Answers

Step-by-step explanation:

Weight of the puppy at 4 weeks old:

\large{11 (1)/(4) } pounds = \large{ (45)/(4) } pounds

This weight is 3/5th times of the weight of puppy in 16 weeks. Let's assume the weight of puppy in 16 weeks be x. Then, 3/5th of x is 45/4 pounds.

Inequationform,

\boxed{ \large{(3)/(5) x = (45)/(4) }}

Multiplying 5/3 both sides to isolate x on LHS,

\large{x = (45)/(4) * (5)/(3) }

\large{x = (75)/(4) = 18.75} pounds

The equation used for finding the weight of puppy is 3x/5 = 45/4. And Jayden's puppy weighed 18.75 pounds in 16 weeks.

The formula F = ma shows the relationship between force, mass, and acceleration. Solve this formula for a.

Answers

Answer:

Solution is a=(F)/(m)

Step-by-step explanation:

We have Force, F = Mass x Acceleration.

That is        F = m x a

Dividing both sides by (1)/(m)

We will get

      (1)/(m)* F=(1)/(m)* m* a\n\n(F)/(m)=(m* a)/(m)\n\n(F)/(m)=(m)/(m)* a\n\na=(F)/(m)

Solution is a=(F)/(m)

The formula you would use to find acceleration would be A= f/m

Solve for
a. 7a-2b = 5a b

Answers

For this case we have the following expression:

From here, we must clear the value of a.

We then have the following steps:

Place the terms that depend on a on the same side of the equation:

Do common factor "a":

Clear the value of "a" by dividing the factor within the parenthesis:

Answer:

The clear expression for "a" is given by:

Answer:  The required value of a is (2b)/(7-5b).

Step-by-step explanation:  We are given to solve the following equation for the value of a:

7a-2b=5ab~~~~~~~~~~~~~~~~~~~~~(i)

Since there are two unknowns and only one equation , so the value of a will definitely contain the value of b.

The solution of equation (i) for a is as follows:

7a-2b=5ab\n\n\Rightarrow 7a-5ab=2b\n\n\Rightarrow a(7-5b)=2b\n\n\Rightarrow a=(2b)/(7-5b).

Thus, the required value of a is (2b)/(7-5b).

what is the degree measure of the acute angle formed by the hands of a 12-hour clock that reads exactly 1 o'clock?

Answers

360^o:12=30^o\leftarrow answer

Answer:

30 degrees

Step-by-step explanation:

which equations represent the line that is parallel to 3x − 4y = 7 and passes through the point (−4, −2)? Check all that apply. y = –x + 1 3x − 4y = −4 4x − 3y = −3 y – 2 = –(x – 4) y + 2 = (x + 4)

Answers

Answer:

\text{The equation represent the line that is parallel to 3x - 4y = 7 and passes through the point (-4, -2) is 3x-4y=-4}      

Step-by-step explanation:

Given the equation 3x - 4y = 7

we have to find the equation which represent the line that is parallel to          3x - 4y = 7 and passes through the point (-4, -2)

As parallel lines have same slope therefore we find the slope of given line

3x-4y=7

4y=3x-7

y=(3)/(4)x-(7)/(4)

Comparing above equation with general equation y=mx+c, where m is slope

m=(3)/(4)

\text{The equation of line having slope }(3)/(4)\text{ and passing through the point (-4,-2) is}

y-y'=m(x-x')

y-(-2)=(3)/(4)(x-(-4))

y+2=(3)/(4)(x+4)

4y+8=3x+12

3x-4y=-4

which is required equation.

Option 2 is correct.

5 + 5+10+20+45+56+56+57+76

Answers